GRAMMATICAL COHESION IN WRITING NARRATIVE TEXT AT TENTH GRADE STUDENTS’ AT VOCATIONAL HIGH SCHOOL SMK SWASTA PUTRA JAYA STABAT - Adi Sutrisno and Sumarsih (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2018)
This study aims at analyzing of grammtical cohesion in writing narrative text. It was conducted by using qualitative descriptive. The subject of this research was tenth (X) grade students of SMK Swasta Putra Jaya Stabat. The number of subjects was taken from one classes. which consist of 37 students‟ and the data only take randomly for the sample of this reseach and choose 9 texts of the students‟ writing. The instrument for collecting data was writing Narrative text. The result of the study showed that (1). The grammatical cohesion was found in the narrative text written by the students‟through the applied of the cohesive device in their writing. There were found reference, substitution, ellipsis and conjunction in the students‟writing. (2). Each cohesive device those were found in the narrative text categorize good with the percentage around 58,49 – 72,72%, one categorize excellent with the percentage 81,25%. Substitution device categorize poor with the percentage        0- 2,04%. Ellipsis were poor with percentage around 0 – 8,33%. And conjunction were fair with 27,27 – 48,57%.